2020
DOI: 10.1111/head.14018
|View full text |Cite
|
Sign up to set email alerts
|

Burden of increasing opioid use in the treatment of migraine: Results from the Migraine in America Symptoms and Treatment Study

Abstract: Objective: We sought to assess factors associated with the frequency of self-reported prescription opioid use in persons with migraine, including demographic variables, comorbidities, headache characteristics, and patterns of consultation. Background: Despite the dose-dependent effect of opioids on migraine progression and the association with negative outcomes, migraine treatment often includes opioids. The Migraine in America Symptoms and Treatment Study focuses on individuals with migraine who receive presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This proportion is low compared with a study from Germany, which reported that opioids were one of the most commonly prescribed acute medications (19.1% of acute medication prescriptions), although opioids were generally not recommended in German guidelines ( 18 ). A survey of migraine patients in the US found that 32.5% of respondents with acute prescription medication for headache/migraine in the previous 3 months reported the use of opioids ( 36 ). Besides, in the American Migraine Prevalence and Prevention (AMPP) study, nearly 30% people with migraine included in the study were either previous users of opioids, or were current opioid users.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is low compared with a study from Germany, which reported that opioids were one of the most commonly prescribed acute medications (19.1% of acute medication prescriptions), although opioids were generally not recommended in German guidelines ( 18 ). A survey of migraine patients in the US found that 32.5% of respondents with acute prescription medication for headache/migraine in the previous 3 months reported the use of opioids ( 36 ). Besides, in the American Migraine Prevalence and Prevention (AMPP) study, nearly 30% people with migraine included in the study were either previous users of opioids, or were current opioid users.…”
Section: Discussionmentioning
confidence: 99%
“…Migraines are a common neurologic condition that can be associated with periods of intense pain, though treatment options are limited. Although opioids are not currently recommended for the management of migraine‐associated pain, a recent study noted that 31% of patients affected with chronic migraine report either using or maintaining a supply of opioids (Lipton et al, 2021). Such off‐label use of opioids could set the stage for future abuse in vulnerable individuals and highlights the need for more effective strategies for managing the symptoms of this disorder.…”
Section: Expanding the Palette Of Functions Subject To Cholinergic Mo...mentioning
confidence: 99%
“…Data on file. 24,53 modified ICHD criteria, as assessed by the AMS/AMPP diagnostic questionnaire; however, its validity in assessing migraine is wellestablished. 14,15 Additionally, by excluding probable migraine, a sizable portion of those with potentially burdensome disease were excluded.…”
Section: Strengths and Limitationsmentioning
confidence: 99%